Rapid onset of small intestinal perforation after successful steroid treatment in eosinophilic granulomatosis with polyangiitis. Issue 6 (1st November 2016) - Ikeda, Keigo; Takasaki, Yoshinari; Sekigawa, Iwao
Abstract : Eosinophilic granulomatosis with polyangiitis (EGPA) is a disorder characterized by extravascular granulomas, hypereosinophilia, and pulmonary and systemic small-vessel vasculitis. Bowel perforation is a rare but often fatal complication of EGPA. In the present report, we describe a case of small intestinal perforation in a patient with EGPA. Through various examinations, we confirmed the presence of EGPA, and the patient responded well to steroid therapy. However, as the patient's condition subsequently worsened, the small intestine was consequently resected. The patient's overall condition improved thereafter. Thus, we believe that careful attention should be paid to intestinal symptoms and perforation in patients with EGPA.